2006
DOI: 10.4314/jasem.v10i3.17323
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>meta</i> - and <i>ortho</i> -cleavage dioxygenases in bacterial phenol-degraders

Abstract: ABSTRACT:In the last five years, in our lab, several bacterial genera capable of degrading phenol as sole carbon source were isolated from different Egyptian ecosystems. Phenol mineralization using these isolates was ranged from 55% to 0.4%. In the present work, randomly chosen representative strains; W-17, DF4 (Acinetobacter), Sea-8 (Stenotrophomonas), W-6 (Klebsiella), S-5 (Bacillus) and W-15 (Ralstonia) were analyzed for the type of ring-cleavage (ortho or meta) dioxygenase physiologically induced during gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…Lack of monooxygenase activity after benzoate induction (data not shown) also confirmed that hypothesis. Among the Stenotrophomonas maltophilia species only one described as strain Sea-8 was found to express catechol dioxygenases activities after phenol induction, although the activity of catechol 2,3-dioxygenase in that case was rather small (28). Contrary to Sea-8 strain, Stenotrophomonas maltophilia strain KB2 growing on 3 mM phenol showed trace activity of intradiol catechol dioxygenase (Table 3).…”
Section: Induction Of the Various Types Of Dioxygenase In Cells Of Stmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of monooxygenase activity after benzoate induction (data not shown) also confirmed that hypothesis. Among the Stenotrophomonas maltophilia species only one described as strain Sea-8 was found to express catechol dioxygenases activities after phenol induction, although the activity of catechol 2,3-dioxygenase in that case was rather small (28). Contrary to Sea-8 strain, Stenotrophomonas maltophilia strain KB2 growing on 3 mM phenol showed trace activity of intradiol catechol dioxygenase (Table 3).…”
Section: Induction Of the Various Types Of Dioxygenase In Cells Of Stmentioning
confidence: 99%
“…A high percentage identity was also found with Stenotrophomonas sp. strain Sea-8, a phenol degrader (28) (Fig. 1).…”
Section: Isolation and Identification Of Strain Degrading Aromatic Comentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results do not mean that the other three isolates QUCASBSD-2, QUCASBSD-4 and QUCASBSD-5 are not 2-chlorophenol degraders. It is known that the degradation of phenol and its derivatives takes place aerobically through two main metabolic pathways; initiated by ortho-or meta-cleavage (Zaki, 2006). The enzymes phenol hydroxylase and catechol 1,2-dioxygenase or 2,3-dioxygenase catalyze the first and the second steps of phenol degradation, respectively (Gaal and Neujahr, 1979) which need to be covered for the isolated strains in next studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, phenols are more commonly produced as artifi cal aromatic compounds in wastewater from many industries, such as textile, dye, oil refi nery, chemical instalation, and medical (Lee et al, 1997;Tsai et al, 2005;Al-Thani et al, 2007;Anonim, 2008). Phenol is relatively soluble in water, and the wastewater containing this compound can contaminate and accumulate in soil, surface water, and ground water (Zaki, 2006;Mahiuddin et al, 2012). This corrosive compound can be absorbed through inhalation, digestion, also skin, and may cause chemical burn, promotes tumor (Bitton, 2005;Anonim, 2008;Chakraborty et al, 2010), also affect the function of human and animal hormonal system (Aoyama et al, 2012).…”
Section: Introductionmentioning
confidence: 99%